Classification system for inter-modular connections in non-sway corner-supported steel modular buildings. (March 2023) - Farajian, M.; Sharafi, P.; Eslamnia, H.; Bai, Y.; Samali, B.
Abstract: The main difference between the structural design of corner-supported modular buildings with their conventional counterparts lies in the design of their connections. This is because of the different configurations and lack of continuity in joints, resulting in a complex boundary condition for predicting the behaviour of these structures. Because of the ever-increasing demand for building construction using these systems, and a relatively large variety of modular connection types being used in practice, it is of paramount importance to provide criteria ensuring the safety and predictability of the stability performance of these structures. This paper proposes a classification system for horizontal and vertical inter-connections in non-sway frames in terms of stiffness and strength for their rotational components. From the stiffness point of view, the boundaries between rigid and semi-rigid zones are identified and formulated with respect to the variation of relative bending stiffness ratios of elements in joints, such as beams, columns, and connections. Two performance criteria are considered for the classification of inter-modular connections in non-sway corner-supported modular buildings: (i) buckling criterion, where general governing equations for buckling analysis are derived for an idealised and simplified model of braced frame corner-supported modular steel building to classify inter-connections based on the ultimate limit state; and (ii) displacement/drift criterion, for which parametric modelling is conducted using OpenSees for classification based on serviceability limit state. From the strength point of view, the inter-connections are classified into three categories namely, fully-strength, partially-strength, and nominally-pinned based on their ultimate moment capacity. The results are then verified in a case study through the use of data for some existing modular inter-connections, from the literature. Finally, based on the findings of this study, some recommendations for the design of inter-modular connections in non-sway corner-supported modular buildings are presented.